Recombinant PASylated nanobody probes with improved blood circulation and tumor targeting - Yicheng Yang; Lingyue Jin; You Zhang; Siyu Zhou; Weijun Wei; Gang Huang; Changfeng Wu (Journal of Innovative Optical Health Sciences)
Nanobodies have been extensively demonstrated in biomedical imaging and therapy. However, nanobody probes often suffer from rapid renal clearance due to its small size. Herein, we reported a recombinant nanobody with a 200 amino-acid polypeptide chain consisting of Pro, Ala, and Ser (PAS) at the C-terminal, which can be easily expressed in Escherichia coli with a high yield. The PASylated nanobody was functionalized with a fluorescent dye and the cell labeling properties were characterized by flow cytometry and confocal microscopy. In vivo fluorescence imaging indicated that the PASylated nanobody showed comparable blood circulation time, but [Formula: see text] times higher tumor targeting ability as compared to the PEGylated nanobody of comparable molecular weight. Our findings demonstrate that nanobody PASylation is a promising approach to produce long-circulating nanobody probes for imaging and therapeutic applications.